2020
DOI: 10.1039/d0ta02979c
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of oxygen reduction and evolution by applying a nanoengineered hybrid catalyst on cobalt free electrodes for solid oxide cells

Abstract: A remarkable enhancement of electro-catalytic activity of a cobalt-free (La0.6Sr0.4)0.98FeO3−δ electrode by applying a nanoengineered hybrid catalyst coating via co-infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The perovskite structure material incorporates H 2 O for protonation [25], and cobalt plays an essential role in cathode catalytic activity [26,27]. However, issues such as cobalt evaporation at high temperatures and thermal mismatch between the cobalt-containing cathode and the electrolyte [28,29] have not been adequately addressed till now. As a result, the development of high-performance cathodes free of cobalt is of interest to many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite structure material incorporates H 2 O for protonation [25], and cobalt plays an essential role in cathode catalytic activity [26,27]. However, issues such as cobalt evaporation at high temperatures and thermal mismatch between the cobalt-containing cathode and the electrolyte [28,29] have not been adequately addressed till now. As a result, the development of high-performance cathodes free of cobalt is of interest to many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, solution-based infiltration is the promising method of surface structural modifications, which is the most facile route to fabricate a cathode in the lower temperature range to further improve the cell performance. Particularly, infiltrated CFL is a smart method to accelerate the kinetics of ORR due to combining the advantages of the above-mentioned surface structure modifications. An infiltrating process is flexible, which can not only produce CFL with a single material, but also construct a nanostructured composite CFL with two or more functional materials. These functional materials include MIEC, ionic conductor, and even a combination of electrocatalysts. ,− In general, the porous scaffold possesses superior electrical conductivity, whereas the infiltrated covering has very good durability and remarkable catalytic activity for the oxygen reduction reaction . For example, Ishfaq et al reported a customized nanofilm of Sm 0.5 Sr 0.5 CoO 3‑δ (SSC) catalyst on a LSC electrode via an optimized drying rate, showing 2× increments in cell performance and superior long-term stability compared to the blank LSC cathode .…”
Section: Introductionmentioning
confidence: 55%
“…In the DRT plots shown in Figure c, all of the peaks demonstrated an increase in magnitude as the temperature decreased. Additionally, their characteristic frequencies shifted toward lower values, indicating a thermally activated behavior . This observation suggests that none of the peaks were exclusively associated with gas diffusion processes, which exhibited only a slight temperature dependence.…”
Section: Resultsmentioning
confidence: 99%